Pelatihan Pembuatan Batik Ecoprint di Desa Wringinsongo Tumpang - Ratna Ika Putri; Supriatna Adhisuwignjo; Yulianto Yulianto; Edi Sulistio Budi; Eka Mandayatma; Zaliyah Amalia; Hari Kurnia Safitri; Adi Candra Kusuma (Jurnal Pengabdian kepada Masyarakat Nusantara, 2023)
Wringinsongo Village is located in the western part of the Tumpang District area, which is in the eastern part of the Malang Regency development area, with a beautiful landscape leading to access to Bromo Tengger Semeru National Park. With the current rapid economic growth, it has affected changes in the pattern of livelihoods for the population, including in the trade and service sectors. The development of the local economic sector is supported by creative MSEs, which in this case have constraints, namely a lack of innovation and creativity in product development. The purpose of the community service activities to increase creativity and innovation in developing village superior products is going well by means of ecoprint batik making training in Wringinsongo Tumpang village. The potential that needs to be explored in Wringinsongo village is eco-print batik because there are many women in the village who can be guided to make eco-print batik. Ecoprint batik is made by printing plant parts (leaves, stems, and flowers) to create attractive patterns or motifs. Ecoprint batik is very environmentally friendly and does not cause environmental pollution, so in this community service activity, training activities are carried out for making eco-print batik. With this activity, the Wringinsongo village community gained additional knowledge and increased abilities and skills. The response given by the village community was very good, with the hope that after this community service activity, the community could produce products that could be sold and made into superior products of Wringinsongo village.